SOCIAL AND CLINICAL CHARACTERISTICS OF PATIENTS WITH NON-MUSCLE-INVASIVE BLADDER CANCE - A. D. Kaprin; O. I. Apolikhin; B. Ya. Alexeev; D. A. Roshchin; A. A. Kachmazov; D. V. Perepechin; M. P. Golovashchenko (Сибирский онкологический журнал)
A retrospective analysis of medical records of 581 patients with non-muscle-invasive bladder cancer was carried out. Out of these patients, there were 467 men and 114 women, with a male-to-female ratio of 4:1. Among males, the highest incidence of non-muscle-invasive bladder cancer occurred in age range 45–59 year followed by age groups 60‑74 and 18‑44 years, representing 45.8 %, 33.4 %, and 16 %, respectively. For females, the highest incidence rate was observed in the 60 to 74 age group (58.7 %). Women aged 45‑59 and 75‑90 years represented 26.5 % and 14.3 %, respectively. The proportion of women aged 45‑49 years was almost half the proportion of men of this age group. Among female patients, there were very few women under 44 years. The vast majority of patients were residents of the Central Federal District with a primary residence in Moscow and the Moscow region. Both male and female patients were more susceptible to negative effects of smoking. Both male and female patients experienced occupational exposure to chemical carcinogens, with 3:1 male predominance. Men represented a higher proportion of those who received radiation therapy as compared to women (3.2 % versus 1.9 %). The bladder wall was the most frequent site of tumor location. The bladder fundus invasion occurred two times less frequently. The frequency of the bladder neck and apex invasion was 13 % and 9 %, respectively. Multicentric bladder cancer was observed in 6 % of the patients. Grade 1 cancer was the most common (53 %) followed by grade 2 and grade 3 (29 % and 18 %, respectively). According to results obtained, the studied cohort demonstrates the main social and clinical characteristics for patients with non-muscle-invasive bladder cancer.